On-axis pulsed laser deposition of hybrid perovskite films for solar cell and broadband photo-sensor applications - Bansode, Umesh; Ogale, Satishchandra B. (Journal of Applied Physics, 2017)
High quality hybrid perovskite films are grown by the pulsed laser deposition (PLD) process through target stoichiometry and gas ambient control in the commonly used on-axis geometry which is compatible with PLD of other materials such as metal oxides. The use of an off-stoichiometric target and a momentum softening gas mixture of argon and hydrogen (90%:10%) is shown to yield dense films in the on-axis geometry with excellent stoichiometry and optical quality. The band gap can be easily tuned from 1.6 to 2.3 eV with either mixed halide composite target or successive depositions of inter-diffusing MAPbBr(3) and MAPbI(3) layers. A photosensor based on PLD grown MAPbI(3) is shown to render impressive performance over the broad range of wavelengths from 375 to 800 nm at a voltage of 5V bias. A planar heterojunction solar cell based on the dry-processed on-axis PLD grown film exhibits a champion conversion efficiency of 10.9%. A heterostructure comprising in situ pulsed laser deposited Cu2O (p-type) followed by the hybrid perovskite film shows a rectifying characteristic and photoresponse.